(untitled) (Journal of Tourism and Hospitality Education, 2019)
Tourism and hospitality industry today, is changing significantly with the application of information technology in its fundamental to strategic activities. It is driven by the competition inherent within the industry as well as the evolving innovative ideas and practices. So, to match the competitive environment and to catch the changing disruption, use of information technology is inevitable. This study reviews the previous research studies related to the information technology (IT) in tourism and hospitality industry with the aim of assessing the recent changes and applications of IT in the industry. Particularly, seven major tourism and hospitality journals published in the last 10 years are reviewed which included 64 research articles relevant to IT in tourism and hospitality industry. The content analysis of the articles is categorized into three major themes, namely: fundamental purpose, internal business process or process redesign and value creation & competitive advantage. The study showed that IT in tourism and hospitality industry is most commonly used in fulfilling information need, studying behavior & performance, managing operation process and innovation process. The use of IT in promotion & marketing, customer management process and value creation & competitive advantage is yet to be explored.